“...JUNTOS Y A SON DE CAMPANA CONGREGADOS”: ELITE’S PRESTIGE AND SOCIABILITY IN SANTIAGO’S BROTHERHOODS (1700-1770) - Ovalle Letelier, Alex (Revista de Historia Social y de las Mentalidades, 2024)
This article analyzes the social practices  regarding three “cofradías” in Santiago, which  received the city elite between 1700 an 1770  and having as a starting point the influences  underlying the institutional structure, which  were represented in the political field and in the  brotherhood administration. The “cofradías” are regarded as  social instances which made social prestige,  possible and worth demonstrating. Its  administration and charity are part of the  distinguishing strategies which the elites in  Santiago would adopt during the firs half of  the XVIII century
Keywords: Cofradías; social prestige; Elite; Santiago de Chile; XVIII century